Liturgy and the Senses - Pickstock, Catherine (The South Atlantic quarterly, 2010)
The impulse to worship precedes philosophical reflection about God. It involves gratitude, admiration, and petition. However, it can also be argued that worship concludes and completes human abstract reflections. First, human beings are called to rise above their animal nature to a spiritual level (Plato). But the church fathers taught that they must rise above intellectual contemplation to union with God through perfected desire. However, we cannot reach this union through our own efforts; God must reach graciously down to us. But when he does so, he reaches down into our entire microcosmic nature; hence, it is the resurrected body that will enjoy the fullness of the beatific vision. Hence also, grace comes to us in sacramental modes of worship and not in isolated solitude. It reaches us through our individual bodies and within the collective body. Beyond the heightened reach of mind alone, God descends to permeate our entire personal being, body and soul. Second, liturgy completes thought because the governing of our senses by reason was disturbed by the fall of Adam. Disordered reason cannot recover this ordering, but our senses remain relatively innocent, like animals and inanimate reality. Many of the fathers and Thomas Aquinas held that fallen reason must be humbled and reeducated through the senses themselves. In the absence of human rational government, the divine Logos itself descends into the human sensory order, supremely in the Eucharist. In the liturgy our senses become rightly attuned, and their immediate intuitions anticipate our seeing God and ourselves through the divine intuition itself in the beatific vision. These rightly attuned senses then reeducate our minds and allow them to become adjusted once more and to fulfill further their contemplative calling.